Tantangan Mahasiswa Studi Islam dalam Menulis Karya Tulis Ilmiah (Studi Kasus pada Mahasiswa Pascasarjana Universitas Islam Madinah) - Muhammad Ar Rafi Yahya (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
Academic writing is a fundamental component of higher education, particularly for postgraduate students in Islamic studies, where scientific writing serves as a medium for preserving, developing, and disseminating knowledge. However, many students still encounter difficulties in translating theoretical understanding into effective academic writing practice. This study aims to analyze the understanding and challenges faced by postgraduate students of the Islamic University of Madinah in writing academic scientific papers. The research employs a qualitative approach using in-depth interviews with students from various study programs. The collected data were analyzed descriptively to reveal students’ perceptions, experiences, as well as internal and external factors influencing the process of academic writing. The findings indicate that students generally possess a good understanding of the nature of scientific writing, including the distinction between scientific and non-scientific works in terms of objectives, methods, content, and language. However, in practice, they continue to face various challenges, both internal and external. Internal challenges include low self-confidence, limited writing habits, weak time management, procrastination, and insufficient proficiency in academic Arabic. Meanwhile, external challenges involve limited access to relevant references, inadequate guidance and training in academic writing, and the lack of a consistently established reading and writing culture within the campus environment. This study highlights the importance of strengthening academic culture, providing continuous mentoring, and developing academic writing skills to improve the quality of scientific works produced by students of Islamic studies. Keywords: Academic Challenges, Islamic Studies, Islamic University Of Madinah, Scientific Writing